Evaluating the effectiveness of a collaborative querying environment - Fu, Lin (2009)
Collaborative querying seeks to help users formulate queries by sharing expert knowledge or other users’ search experiences. In previous work, a collaborative query environment (CQE) was developed for a digital library. The system operates by clustering and recommending related queries to users using a hybrid query similarity identification approach. Users can explore the query clusters using a graph-based visualization system known as the Query Graph Visualizer (QGV). The purpose of this paper is to evaluate the CQE with goal of informing the usefulness and usability of such a system. Our results show that compared with traditional information retrieval systems, collaborative querying can lead to faster information seeking when users perform unspecified tasks.